2022
DOI: 10.1161/hypertensionaha.122.19414
|View full text |Cite
|
Sign up to set email alerts
|

Digital Therapeutics in Hypertension: Evidence and Perspectives

Abstract: Digital therapeutics refers to the use of evidence-based therapeutic interventions driven by high-quality software programs to treat, manage, or prevent a medical condition. This approach is being increasingly investigated for the management of hypertension, a common condition that is the leading preventable cardiovascular disease risk factor worldwide. Digital interventions can help facilitate uptake of important guideline-recommended lifestyle modifications, reinforce home blood pressure monitoring, decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Hypertension accounts for the largest number of deaths worldwide and is particularly harmful to the blood vessel, heart, kidney, and brain. Hypertension is closely associated with unhealthy dietary habits, such as heavy alcohol consumption, excessive intake of sodium salt, and low potassium diet ( 3 ). A better understanding of the relationship between the risk of hypertension and dietary habits is essential to prevent the onset and development of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension accounts for the largest number of deaths worldwide and is particularly harmful to the blood vessel, heart, kidney, and brain. Hypertension is closely associated with unhealthy dietary habits, such as heavy alcohol consumption, excessive intake of sodium salt, and low potassium diet ( 3 ). A better understanding of the relationship between the risk of hypertension and dietary habits is essential to prevent the onset and development of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…A metaanalysis on the effect of home BP monitoring demonstrated that home BP monitoring with the education and/or consultation significantly lower BP [20]. In 2021, the first randomized control trial of digital therapeutics (application) for hypertension (HERB-DH1) demonstrated the significant 24-h SBP reduction, compared with control group [21,22]. Both digital therapeutics group and control group received doctor's routine lifestyle education with home BP morning.…”
Section: Proposal Of Home Bp-centered Approachmentioning
confidence: 99%
“…Both digital therapeutics group and control group received doctor's routine lifestyle education with home BP morning. Morning home SBP significantly reduced by 10.9 mmHg in digital therapeutics group, and by 6.2 mmHg in the control group (the group-difference: 4.3 mmHg, p < 0.001) [21,22]. In 2022, in Japan, the digital therapeutics of hypertension was first approved by regulatory authority in the condition of combined use of home BP monitoring [23].…”
Section: Proposal Of Home Bp-centered Approachmentioning
confidence: 99%
“…Digital Therapeutics (DTx), a subset of digital health solutions, provides evidence-based therapeutic interventions. To prevent, manage, or treat a medical ailment, DTx leverages state-of-the-art artificial intelligence techniques to replace or enhance a variety of established psychological approaches to therapy ( 6 ). Artificial intelligence techniques have been widely employed in a variety of fields and have already been used in combination with drugs or other therapies to improve patient care and health outcomes ( 7 12 ).…”
Section: Introductionmentioning
confidence: 99%